2011
DOI: 10.1016/j.jsha.2011.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cardiac involvement of hepatitis C virus; tissue Doppler imaging and NTproBNP study

Abstract: This data show the first direct evidence that HCV infection causes diastolic dysfunction without any other predisposing factors, probably due to chronic inflammatory reaction with mild fibrosis in the heart. Previous studies did not follow strict inclusion and exclusion criteria that confirm the independent role of HCV to cause diastolic dysfunction. Tissue Doppler was more sensitive to diagnose diastolic dysfunction than conventional Doppler.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
1
10
0
2
Order By: Relevance
“…According to literature, in our study we found a significant increase in cardiac mass, atrial volume and diastolic dysfunction in HCV‐related cirrhotic patients . The increase in left ventricular mass is due to volume overload secondary to expansion of blood volume and activation of neuro‐hormonal systems commonly observed in these patients .…”
Section: Discussionsupporting
confidence: 69%
“…According to literature, in our study we found a significant increase in cardiac mass, atrial volume and diastolic dysfunction in HCV‐related cirrhotic patients . The increase in left ventricular mass is due to volume overload secondary to expansion of blood volume and activation of neuro‐hormonal systems commonly observed in these patients .…”
Section: Discussionsupporting
confidence: 69%
“…In addition to hepatitis, hepatitis C virus (HCV) infection frequently causes cardiac and renal abnormalities, including hypertrophic cardiomyopathy and DCM. In Egypt, in patients with HCV infection, echocardiographic abnormalities were frequently found, such as dilated left atrium, dilatation and hypertrophy of the left ventricle and disturbed diastolic and systolic function of the left ventricle 206 . In China, NT-proBNP levels are higher in patients with HCV-infection-associated hepatitis than in those with hepatitis B virus infection or in healthy controls 207 .…”
Section: Inflammationmentioning
confidence: 99%
“…Data entry, processing and statistical analysis was carried out using MedCalc ver. 18 Inferential statistics carried out using (Chi square, independent student's t test, and Spearman correlation coefficient).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of, Saleh et al, 2011, who reported that, the first direct evidence that HCV infection causes diastolic dysfunction without any other predisposing factors, probably Diabetic Patients with Hepatitis C Virus (HCV) due to chronic inflammatory reaction with mild fibrosis in the heart. Previous studies did not follow strict inclusion and exclusion criteria that confirm the independent role of HCV to cause diastolic dysfunction [18].…”
Section: Discussionmentioning
confidence: 99%